Recent warming at Summit, Greenland: Global context and implications. Issue 10 (20th May 2013) - McGrath, Daniel; Colgan, William; Bayou, Nicolas; Muto, Atsuhiro; Steffen, Konrad
Abstract [1] Observations at Summit, Greenland suggest that the annual mean near‐surface air temperature increased at 0.09 ± 0.01°C/a over the 1982–2011 climatology period. This rate of warming, six times the global average, places Summit in the 99th percentile of all globally observed warming trends over this period. The rate of warming at Summit is increasing over time. During the instrumental period (1987–2011), warming has been greatest in the winter season, although the implications of summer warming are more acute. The annual maximum elevation of the equilibrium line and dry snow line has risen at 44 and 35 m/a over the past 15 and 18 years, respectively. Extrapolation of this observed trend now suggests, with 95% confidence intervals, that the dry snow facies of the Greenland Ice Sheet will inevitably transition to percolation facies. There is a 50% probability of this transition occurring by 2025.